The liberation era in ligao and the aftermath of world war II 1944-1945 - Mendoza, Delia V. (San Miguel, Iriga City: University of Saint Anthony, 2015)
The liberation era in ligao and the aftermath of world war II 1944-1945.
Includes bibliographical references.
English
Keywords: Liberation